Meningkatkan Hasil Belajar tentang Hak, Kewajiban dan Tanggung Jawab sebagai Warga Negara dengan Media Video Pembelajaran pada Siswa Kelas V B SDN 003 Lubuk Baja - Yuraini Yuraini (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
This study aims to find out how to improve learning outcomes about rights, obligations and responsibilities as citizens by using learning videos for students, and whether the use of learning video media can increase students' understanding of rights, obligations and responsibilities as citizens. used is classroom action research (CAR). This method is carried out through 4 stages, namely planning, implementation, observation and reflection. The results showed that the average value obtained from classical data was 83.4 students completed as many as 29 people, 10 students did not complete with a predetermined KKM of 82, with a percentage of completeness reaching 74.4% while students who did not complete by 25.6%. In Cycle II it was found that the classical average reached 87.2 students completed as many as 32 people, students did not complete and 7 students with a predetermined KKM were 82, with a percentage of completeness reaching 82.05% while students who did not complete were 17, 95%. The percentage of teacher activity in Cycle I has increased by 81.25%, of the 16 indicator items observed, teachers in Cycle I were able to implement 13 indicators, while the remaining 3 indicators were not implemented, in Cycle II teacher activity reached the highest score between Cycle I and Cycle I and Cycle II. Cycle II with an activity percentage of 93.75%, from 16 observed indicator items. Thus it can be concluded that the use of learning video media can improve student learning outcomes about rights, obligations and responsibilities as citizens.